Experimentally Validated Vector Lyapunov Function-Based Iterative Learning Control Design Under Input Saturation - Pakshin, Pavel; Mandra, Sławomir; Emelianova, Julia; Rogers, Eric; Erwiński, Krystian; Gałkowski, Krzysztof
This paper addresses the problem of input saturation in iterative learning control, a problem area that has seen relatively little research effort. A new design is developed based on a branch of 2D systems theory, and, in particular, Lyapunov based stability theory. The resulting design is compared in simulation with an alternative. In the final part of the paper the results of an in depth experimental investigation of the new designs properties are reported.
Keywords: control input saturation; iterative learning control (ILC) design; repetitive processes; vector Lyapunov functions